Plantago ovata as a low-cost community-based dietary fibre intervention: a narrative review of evidence and public health applications - Mohammad Bilal; Rayyan Moin; Syed Sohaib Hashmi; Ali Jafar Abedi; Uzma Eram (International Journal Of Community Medicine And Public Health, 2026)
Dietary fibre is an important but often underemphasized component of preventive nutrition and community health practice. Plantago ovata Forssk., commonly known as psyllium or Isabgol, is a soluble, gel-forming fibre widely used in South Asia and traditionally described in Unani dietotherapy as a demulcent and bulk-forming agent for digestive balance. A narrative review was conducted to synthesize traditional Unani descriptions and contemporary biomedical evidence on Plantago ovata, with emphasis on gastrointestinal and metabolic outcomes and public health applications. Literature was searched in PubMed, PubMed Central, Google Scholar, Scopus and Web of Science, with a supplementary search updated in May 2026. Evidence from randomized controlled trials and meta-analyses supports psyllium for improving stool frequency and consistency among adults with constipation, with additional modest benefits on low-density lipoprotein cholesterol and selected glycaemic indices. Its physiological effects are related to water-holding capacity, stool bulking, delayed glucose absorption, bile acid binding and possible modulation of gut microbiota. Psyllium has practical relevance as a low-cost, culturally familiar and generally safe adjunct that can be incorporated into dietary counselling at primary care and community levels. Public health messages should emphasize food-based fibre intake, adequate fluid intake, gradual introduction, medication spacing and recognition of warning symptoms.